Gereja Sinodal dalam Terang “In Illo Uno Unum” - Winarto, Heribertus (Institutum Ioannis Mariae Vianney Surabayanum, 2025)
This study offers a theological–ecclesiological analysis of synodality in light of Pope Leo XIV’s programmatic motto In Illo Uno Unum (“In the One, we are one”). Drawing upon Augustinian ecclesiology and recent magisterial developments, the paper argues that synodality constitutes not merely an institutional mechanism but an essential modality of the Church’s self-understanding as the communio of God’s pilgrim people. By situating Pope Leo XIV’s vision within the broader trajectory of conciliar tradition—especially the legacy of Nicaea in its 1700th anniversary—the study highlights the intrinsic link between synodality, ecclesial unity, and ecumenical rapprochement. It further examines synodality as an ecclesial form of discernment ordered to the missio Dei, whereby the Church participates in Christ’s Paschal dynamic through listening, dialogue, and co-responsibility. Finally, the paper presents synodality as a mode of prophetic witness capable of addressing contemporary socio-political fragmentation by promoting reconciliation, peace, and the dignity of every human person. Thus, synodality emerges as a comprehensive paradigm for renewing the Church’s communion and mission in the third millennium.